Bioinformatic Analysis Reveals Hub Immune-Related Genes of Diabetic Foot Ulcers - Rong, Yanchao; Yang, Hao; Xu, Hailin; Li, Shuting; Wang, Peng; Wang, Zhiyong; Zhang, Yi; Zhu, Wenkai; Tang, Bing; Zhu, Jiayuan; Hu, Zhicheng (Frontiers in Surgery, 2022)
Diabetic foot ulcer (DFU) are a complex and devastating complication of diabetes mellitus that are usually stagnant in the inflammatory phase. However, oral wound healing, which is characterized by a rapid and scarless healing process, is regarded an ideal model of wound healing. Thus, we performed a comprehensive bioinformatics analysis of the previously published data regarding oral ulcers and DFUs and found that compared to oral wound healing, the activated pathways of DFUs were enriched in cellular metabolism-related pathways but lacked the activation of inflammatory and immune-related pathways. We also found that CXCL11, DDX60, IFI44, and IFI44L were remarkable nodes since they had the most connections with other members of the module. Meanwhile, CXCL10, IRF7, and DDX58 together formed a closed-loop relationship and occupied central positions in the entire network. The real-time polymerase chain reaction and western blot was applied to validate the gene expression of the hub immune-related genes in the DFU tissues, it was found that CXCL11, IFI44, IFI44L, CXCL10 and IRF7 have a significant difference compared with normal wound tissues. Our research reveals some novel potential immune-related biomarkers and provides new insights into the molecular basis of this debilitating disease.